1982
DOI: 10.1128/jb.151.1.420-428.1982
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis has penicillin-binding proteins but not detectable muramic acid

Abstract: Chlamydia trachomatis LGV-434 was grown in HeLa 229 cells. Benzylpenicillin completely inhibited the formation of infectious elementary bodies (EBs) at a concentration of 19 pmol/ml or higher and produced abnormally large reticulate bodies (RBs) in the inclusions at 30 pmol/ml or higher. The possible targets for penicillin in C. trachomatis were three penicillin-binding proteins (PBPs) which were identified in the Sarkosyl-soluble fractions of both RBs and EBs. The apparent subunit molecular weights were 88,00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(75 citation statements)
references
References 43 publications
1
73
0
1
Order By: Relevance
“…Thus, synthesis of the cysteine-rich proteins associated with RB-EB differentiation [20][21][22], whose expression is under strict gene regulation [23], may well have been impaired [1]; these proteins have been reported absent from penicillin-induced chlamydial forms [23,24]. A possible explanation for our findings may be that under amino acid limitation chlamydial multiplication is affected by interference with the expression of genes encoding the penicillin-binding proteins [25] -enzymes known to be involved in envelope expansion and septum formation in other bacteria, and suggested to be functionally active in Chlamydia [25]. Indeed, changes in bacterial shape, peptidoglycan properties and synthesis of penicillin-binding proteins have been reported for Escherichia coli growing at reduced rate [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, synthesis of the cysteine-rich proteins associated with RB-EB differentiation [20][21][22], whose expression is under strict gene regulation [23], may well have been impaired [1]; these proteins have been reported absent from penicillin-induced chlamydial forms [23,24]. A possible explanation for our findings may be that under amino acid limitation chlamydial multiplication is affected by interference with the expression of genes encoding the penicillin-binding proteins [25] -enzymes known to be involved in envelope expansion and septum formation in other bacteria, and suggested to be functionally active in Chlamydia [25]. Indeed, changes in bacterial shape, peptidoglycan properties and synthesis of penicillin-binding proteins have been reported for Escherichia coli growing at reduced rate [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Work from the laboratory of Caldwell demonstrated that Chlamydia possesses three Pbps (Barbour et al, 1982). The sequencing of the first chlamydial genome, C. trachomatis serovar D, identified two HMW Pbps annotated as Ct270 and Ct682 (Stephens et al, 1998).…”
Section: Bioinformatics Analysis Of the Hmw Pbps Of Chlamydiamentioning
confidence: 99%
“…The function of the HMW Pbps is to catalyse the polymerization of the PG subunits (Ghuysen and Goffin, 1999). The presence of Pbps and the sensitivity of chlamydiae to penicillin were surprising given that no peptidoglycan (PG) has yet been detected in the bacteria (Barbour et al, 1982). Moulder (1993) referred to this as the 'Chlamydial Anomaly'.…”
Section: Introductionmentioning
confidence: 99%
“…The disulfide bonds form an extensive intermolecular network that increases the structural rigidity of the outer membrane. [22][23][24] The intermolecular network at the outer membrane is called chlamydial outer membrane complex (COMC) and is thought to substitute for the very limited amount of chlamydial cell wall peptidoglycan, a component that provides rigidity and structural strength against osmotic pressure to the wall of Gram-negative bacteria. 22 The major constituents of COMC are MOMP and two cysteine rich proteins OmcA and OmcB.…”
Section: Introductionmentioning
confidence: 99%